Sustainable production of a highly pure (R,R)-2,3-butanediol from crude glycerol using metabolically engineered Klebsiella pneumoniae GEM167 strain - Min-Ho Jo; Jung-Hyun Ju; Sun-Yeon Heo; Ki Jun Jeong; Baek-Rock Oh (Chemical and Biological Technologies in Agriculture)
Abstract Background Among 2,3-butanediol (2,3-BDO) stereoisomers, (R,R)-2,3-BDO is particularly noteworthy for its application in the agricultural industry. It is an eco-friendly plant immune system stimulant, promoting plant growth and enhancing resistance to biotic and abiotic stresses. Results This study aimed to address the limitations of a previous study, which produced (R,R)-2,3-BDO with only 98% purity despite Kp-dhaD overexpression. First, BLi-gldA demonstrated significantly higher activity and selectivity in converting racemic acetoin to (R,R)-2,3-BDO compared to others among 2,3-BDO dehydrogenases (Kp-dhaD and Kp-gldA from Klebsiella pneumoniae, and BLi-gldA from Bacillus licheniformis). The K. pneumoniae GEM167 ΔadhEΔldhAΔbudC-BLi-gldA/pETM6 strain produced the highest (R,R)-2,3-BDO amount, with 99% purity (73.51 ± 1.69 g/L at 48 h), by isopropyl β-D-1-thiogalactopyranoside addition at the early exponential growth phase (6 h) compared to other cell growth phases. The availability of crude glycerol was investigated, and crude glycerol promoted cell growth resulting in efficient (R,R)-2,3-BDO in the early stage of culture [90.32 ± 1.12 g/L (R,R)-2,3-BDO with 99.0% purity after 60 h]. The productivity and yield remained comparable for crude glycerol (1.51 g/L/h, 0.41 g/g) and pure glycerol (1.53 g/L/h, 0.43 g/g). Conclusions This study successfully produced 99% enantiopure (R,R)-2,3-BDO from crude glycerol for the first time using the K. pneumoniae GEM167 ΔadhEΔldhAΔbudC-BLi-gldA/pETM6 strain. (R,R)-2,3-BDO production from crude glycerol, a biodiesel process byproduct, is expected to contribute to a sustainable and circular biomass supply chain and biodiesel production system by positively influencing the stable cultivation of biodiesel crops even under unpredictable climate conditions. Graphical abstract